2018
DOI: 10.1007/s00167-018-5102-4
|View full text |Cite
|
Sign up to set email alerts
|

Medial patellofemoral ligament reconstruction with or without tibial tubercle transfer is an effective treatment for patellofemoral instability

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
51
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 30 publications
3
51
0
Order By: Relevance
“…It is now well established that TTM and isolated MPFLR are effective procedures to treat RPD [15][16][17], but these approaches are also imperfect. In terms of MPFLR, Shah et al [18] revealed an overall cumulative complication rate of 26.1% when this operation is adopted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is now well established that TTM and isolated MPFLR are effective procedures to treat RPD [15][16][17], but these approaches are also imperfect. In terms of MPFLR, Shah et al [18] revealed an overall cumulative complication rate of 26.1% when this operation is adopted.…”
Section: Discussionmentioning
confidence: 99%
“…Overview of the study groupsCWDFO, MPFLR CWDFO, MPFLR, LRTotal knees14 11 Age (years) 18 (14-27) 20(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) …”
mentioning
confidence: 99%
“…It is now well established that TTM and isolated MPFLR are effective procedures to treat RPD [15][16][17], but these approaches are also imperfect. In terms of MPFLR, Shah et al [18] revealed that the overall incidence rate of complications was 26.1% when this operation is adopted.…”
Section: Discussionmentioning
confidence: 99%
“…Concomitant MPFLR and TTO result in significant clinical improvement as well as a resolution of patellar tilt. 24…”
Section: Discussionmentioning
confidence: 99%